Using the Interactive Question and Answer Method to Achieve Active Students Involvement in Class X High School Geography Lessons - Tarigan, Betania Br; Susanti, Asih Enggar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Student involvement in the learning process is an important thing in the learning process. This will certainly provide a positive contribution to the success of achieving the learning objectives set by the teacher as well as the learning outcomes for students. Moreover, student involvement in learning can lead students to understand and enjoy every activity or learning experience that has been planned. However, the facts in the field are still found that in the learning process not all students are actively involved when following the learning process. Thus, the learning process needs to use the right method, and in this case the teacher uses the interactive question and answer learning method to strive for active student involvement in learning. The purpose of writing this paper is to explain the steps of the interactive question and answer method to strive for active student involvement in Geography learning in grade X of high school. The method used is descriptive qualitative. The data analysis used is descriptive. The results of the study showed that there are 4 steps in implementing the interactive question and answer method that can strive for student involvement in learning, which consist of (1) the teacher determines the basic competencies to be achieved according to the topic, (2) the teacher and/or students can ask questions, (3) the teacher gives appreciation together with all students involved in learning and (4) the teacher summarizes the answers that have been expressed by students. Thus, it can be concluded that the use of interactive question and answer methods can encourage the active involvement of class X students in Geography lessons.